Experience of Two-Stage Treatment of Rectal Fistulas Using Low-Thrombin Fibrin Glue “Kriofit” - S. А. Frolov; A. M. Kuzminov; D. V. Vyshegorodtsev; V. Yu. Korolik; I. S. Bogormistrov; A. N. Ryndin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to improve the results of treatment of patients with rectal fistula.Materials and methods. Twenty-eight patients with rectal fistulas were included in the study — 20 (71,4 %) men and 8 (28,6 %) women, average age — 40 (24–68) years. Based on examination and transrectal ultrasound data, 13 (46.4 %) patients had intrasphincteric fistulas and 15 (53.6 %) had transsphincteric fistulas. All patients underwent prehospital transrectal ultrasound and sphincterometry to assess the functional state of the anal sphincter, and the SF-36 quality of life questionnaire and Wexner scale assessing the functional status of the anal sphincter were analyzed. All patients, included in the study, had straight fistulous passage, without collections and significant scarring of the anal canal. Patients underwent two-stage surgical treatment using low-thrombin fibrin glue “Kriofit”. Follow-up of the patients was carried out on days 7, 14, 21 and included collection of complaints, examination of the perianal area, finger examination of the rectum. In the postoperative period, the intensity of pain syndrome was assessed using the visual analog scale of pain. On days 30 and 90 control transrectal ultrasound, sphincterometry, assessment of Wexner scale and patients' quality of life by SF-36 questionnaire on days 7 and 30 after the operation were performed. Results. There were no intraoperative and early postoperative complications among patients. The average bed-day was 6.8 (5–11) days. The follow-up periods ranged from 1 to 42 months. Disease recurrences were diagnosed in 3 (10.7 %) patients. According to the sphincterometry data, no anal holding dysfunction was detected in any of 28 patients.Conclusion. The results of our study have shown that the division of preliminary surgical treatment of the fistulous passage followed by local anti-inflammatory treatment and filling of the wound canal with two-component fibrin glue with low thrombin content “Kriofit” into two stages effectively increases the results of the proposed technique. The use of fibrin glue as a sphincter-preserving technique makes it possible to exclude the development of postoperative anal incontinence, and new technologies and materials reduce the risk of disease recurrence.